The Impact of Sustainable Finance on Non-Profit Organizations with a Hybrid Funding and Social Innovation Approach in West Java - Zakiah Annisha (Cita konsultindo, 2025)
This study aims to analyze the impact of sustainable finance on non-profit organizations in West Java using a hybrid funding and social innovation approach. Sustainable finance, which involves the efficient and responsible management of resources, plays a crucial role in ensuring the operational sustainability of non-profit organizations. The hybrid funding approach, combining funds from various sources such as donations, social investments, and public sector financing, is expected to enhance the financial resilience of non-profits. Additionally, social innovation, as a key element in non-profit sustainability strategies, can strengthen the social impact generated. The research method employed is quantitative with a survey approach. Data were collected through questionnaires distributed to managers of non-profit organizations in West Java that utilize a hybrid funding model. Data analysis was conducted using linear regression to measure the influence of sustainable finance variables on the performance of non-profit organizations, considering the role of social innovation as a moderating variable. The results of the study are expected to provide insights into the effectiveness of hybrid funding in creating financial and social sustainability for non-profit organizations, as well as highlight the importance of social innovation in supporting the achievement of broader social goals. These findings are also expected to offer recommendations for non-profit organizations in West Java in designing more effective and innovative sustainable financial strategies.